George Orwell and 1984: a personal view - ALFREDO SANDOVAL GÓMEZ (Universidad del Magdalena, 2013)
George Orwell´s 1984 is considered a great negative utopia, in the sense it depicts the nightmare of what life might become in an oligarchic collectivism pursued to its logical conclusion. Under a social setup which is nothing but totalitarian barbarism, eternal warfare is the price one pays for an elusive peace. The Party with capital P keeps a total control over all of man´s actions as well as thoughts . The novel is a great satire and it attempts to diagnose man´s alienation in all its aspects, but with special emphasis on the social organization recommended by Marx and practiced by Stalin.